Steroid refractory giant cell arteritis with bilateral vertebral artery occlusion and middle cerebellar peduncle infarction. (2019) - Healy, Sarah; Simpson, Mark; Kitchen, William J; Jacob, Anu; Crooks, Daniel; Rathi, Nitika; Biswas, Shubhabrata; Fletcher, Nicholas; Huda, Saif; Sekhar, Alakendu
No abstract available